2009
DOI: 10.1007/s10562-009-9861-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Microwave-Assisted Deposition for the Synthesis of Noble Metal Particles on Ti-Containing Mesoporous Silica

Abstract: A facile and unique methodology to synthesize the nano-sized and uniform noble metal (Pt and Au) particles has been developed using mesoporous silica support including single-site titanium oxide moieties (Ti-HMS) under microwave irradiation. Characterization by CO adsorption, XAFS, and TEM analysis revealed that the size of metal particles depends on the preparation methods and that the smaller sizes of metal particles were formed on the microwave-assisted metal catalysts compared to the conventionally prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It can be observed that, due to the various natures of the noble metal, different morphologies of Au-NPs confined among the channels of mesoporous silicas can be formed. Meanwhile, another facile and unique methodology to synthesize the nanosized and uniform noble metal (Pt and Au) nanoparticles has been developed using mesoporous silica support including single-site titanium oxide moieties (Ti-HMS) under microwave irradiation [48]. Physical characterizations reveal that the smaller size of metal particles is formed on the microwave-assisted Ti-HMS support compared to the conventionally prepared impregnated samples.…”
Section: Other Novel Synthesis Of Au/mesoporous Silicamentioning
confidence: 99%
“…It can be observed that, due to the various natures of the noble metal, different morphologies of Au-NPs confined among the channels of mesoporous silicas can be formed. Meanwhile, another facile and unique methodology to synthesize the nanosized and uniform noble metal (Pt and Au) nanoparticles has been developed using mesoporous silica support including single-site titanium oxide moieties (Ti-HMS) under microwave irradiation [48]. Physical characterizations reveal that the smaller size of metal particles is formed on the microwave-assisted Ti-HMS support compared to the conventionally prepared impregnated samples.…”
Section: Other Novel Synthesis Of Au/mesoporous Silicamentioning
confidence: 99%
“…55,56 Physical irradiation methods, such as synchrotron X-ray irradiation, microwave heating, and sonication have emerged recently to reduce Au on TiO 2 supports. 32,33,57 The advantage of the synchrotron method was that the resultant Au NPs had a uniform size distribution of 2-5 nm and a much shorter time (e.g. exposure time of 1-15 min) was required to obtain fully reduced Au NPs, in comparison with conventional chemical or photochemical methods.…”
Section: Addition Of Au Nanoparticles To Tiomentioning
confidence: 99%
“…[108][109][110][111] Recently, we have found that Ti-HMS also acts as a promising platform to deposit uniform and small metal particles, such as Pt and Au, under microwave irradiation. 112 The detailed mechanism of the formation of the noble metal particles on single-site photocatalysts has been investigated as future work.…”
Section: Hollow Magnetic C-fe 2 O 3 Nanospheresmentioning
confidence: 99%